Pengontrol Lampu Berbasis IoT dengan Arduino untuk Pencegahan Penularan Covid-19 - Aristiyana, Fadil Danu; Nugroho, Feri; Wilyanti, Sinka; Sari, Ribut Nawang; Satriadi, Indra (Jurnal Informatika Universitas Pamulang, 2023)
With the Covid-19 virus pandemic that has plagued various countries, the need for a system to prevent transmission of the virus is very important. By utilizing IoT technology to be applied to light control systems, it can reduce the spread of the Covid-19 virus. The design of this IoT-based light control system is carried out using the Android application and the Arduino Uno via a Wifi connection and using a PIR sensor that can be connected to the ESP8266 Wifi module. With the PIR motion sensor, it can be implemented as a controller of light intensity with 3 brightness differences.